Affiliate Marketing Strategies in Increasing Online Sales - Erislan Erislan (Return : Study of Management, Economic and Bussines, 2024)
Currently, online sales are experiencing rapid development. This can be seen from several internet sites that offer various goods or products presented to buyers. It is not easy to offer goods online, because conventional sales require various strategies. Therefore, sales that are carried out online must also have a strong strategy from conventional sales. Marketing strategy is very important to do in offering goods or services done online. This research uses a type of analytical descriptive research that aims to understand a phenomenon that will be experienced in the research subject, namely how much influence the Affiliator has in marketing the sellers' products through online sites. The results of this study show that Affiliate Marketing marketing strategies, sales, and consumer behavior have a positive and significant effect on consumer behavior. To increase online sales, marketing strategies are needed including 1) Quality of sales products, 2) Price Influence, 3) The Role of Brand Image, 4) Communication with Customers. 5) Return Guarantee.